Activity of magnetite-immobilized catalase in hydrogen peroxide decomposition - Horst, María Fernanda (2006)
The present work analyzes the activity in decomposition of H 2O2 using magnetite-immobilized catalase. The support of catalase is a glutaraldehyde-treated magnetite (Fe3O4). The data obtained in the H2O2 decomposition are analyzed. The fitting of the initial rate of the H2O2 decomposition versus hydrogen peroxide concentration data is discussed using a specific program for enzyme kinetics modeling (Leonora). The free catalase from Aspergillus niger (3.5 or 10 U/mL) does not show substrate inactivation up to 0.4 M H2O2. The immobilized catalase at low catalyst concentration shows substrate inhibition. Using 1 mg/mL of supported catalase the predicted maximum activity is higher than in the case of the free catalase at similar catalase concentration, although the optimum temperature is lower (40°C versus 60°C).